What is going on around the world: major NUS players and ongoing efforts - Padulosi, Stefano; Meldrum, Gennifer; Israel Oliver King. E.D.; Hunter, Danny (Routledge, 2021)
The chapter provides an overview of major projects and initiatives related to the conservation and sustainable use of neglected and underutilized species (NUS) around the world. Each entry has been checked through a visit to the respective website or recent publications in order to ensure the activities are still ongoing. The long list of entries is a testament to the growing interest in NUS in both developed and less-developed economies. Greater synergies among actors and stakeholders engaged in NUS is strongly advocated.